1172 Maggot Debridement Therapy (MDT) In Treating Group A Streptococcus Necrotizing Fasciitis of The Lower Limb as A Part of Multimodal Therapy. (12th October 2021) - Haroon, M; Alsahaf, O; Asure, A; Eguare, E
Abstract: Background: Medical-grade maggots have been commercially available recently and today there is a resurge interest in MDT. They are approved for debridement of wounds with necrotic tissue, including pressure ulcers, venous ulcers. However, for necrotising fasciitis, it has been used with precaution due to the complexity of the disease. In our practice, Maggot debridement therapy (MDT) has been proven to be very effective in the treatment of gram-positive bacterial infections. Worldwide, Case reports on the results of 15 patients with necrotizing fasciitis treated with MDT have been reported. However, in current practice, Maggot Debridement therapy has not been widely applied. Case presentation: A 63-year-old lady admitted to a general surgery ward with uncomplicated cellulitis of the right leg. After 2 days, the patient then was diagnosed with Necrotising fasciitis which was treated with wound debridement. Postoperative histopathology specimen confirmed necrotizing fasciitis V.A.C. VERAFLO™ Therapy was used postoperatively followed by two more debridement sessions. To reduce the need for further surgical debridement Maggot Debridement Therapy was started. Over the next 3 weeks, six sessions of Maggot Debridement therapy were applied to the infected area. Skin grafting then was performed 3 months later. The patient then discharged home with regular surgical fellow up. Conclusions: NF is a complex disease, associated with high morbidity and mortality. Multimodal therapies are essential to achieve aggressive yet conservative wound debridement with preservation of viable tissue. This case report showed that MDT is a feasible, safe, cost-effective option that to be added to the other treatment modalities